Reward-based behaviors and emotional processing in human with narcolepsy-cataplexy - Bayard, Sophie; Dauvilliers, Yves A. (Frontiers in Behavioral Neuroscience, 2013)
Major advances in the past decade have led a better understanding of the pathophysiology of narcolepsy with cataplexy (NC) caused by the early loss of hypothalamic hypocretin neurons. Although a role for hypocretin in the regulation of sleep/wakefulness state is widely recognized, other functions, not necessarily related to arousal, have been identified. Hence, the hypocretin system enhances signaling in the mesolimbic pathways regulating reward processing, emotion and mood regulation, and addiction. Although studies on hypocretin-deficient mice have shown that hypocretin plays an essential role in reward-seeking, depression-like behavior and addiction, results in human narcolepsy remained subject to debate. Most of studies revealed that hypocretin-deficient narcolepsy patients either drug-free or medicated with psychostimulant had preferences toward risky choices in a decision-making task under ambiguity together with higher frequency of depressive symptoms and binge eating disorder compared to controls. However, human studies mostly reported the lack of association with pathological impulsivity and gambling, and substance and alcohol abuse in the context of narcolepsy-cataplexy. Prospective larger studies are required to confirm these findings in drug-free and medicated patients with narcolepsy. Inclusion of patients with other central hypersomnias without hypocretin deficiency will provide answer to the major question of the role of the hypocretin system in reward-based behaviors and emotional processing in humans.